ANALISIS BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING - Alfred Lasarudin; Tanto Gatot Sumarsono; Mokhamad Natsir (Universitas Merdeka Malang, 2021)
This research objected to explain the effect of organizational culture against employee performance through the work motivation as an intervening variable. This research used an explanatory research where the model used in this research was a causality model, which was a study that objected to determine the correlation of a cause and effect between the independent variable and the dependent variable. This location of this research was Ijen Suites Resort Convention Malang in 2020. The respondents in this research were 35 employees of Ijen Suites Resort Convention Malang. During the process of this research, the data was collected by using questionnaire and interview. The data was analyzed by using quantitative analysis method with multiple linear regression whose explanation was carried out with qualitative interpretation. The results of this research concluded that organizational culture affected employee’s performance and their work motivation, the stronger organizational culture that existed in the organization improved the employee’s performance and employee’s motivation. Furthermore, work motivation affected the employee’s performance and intervened the affect of organizational culture against employee performance, which meant that the higher the level of work motivation improved employee’s performance, and employee’s performance could be improved if the company implemented a strong organizational culture to motivate the employees.